Circuito espacial da produção de laticínios e o uso do território: atuação do laticínio Belo Vale - ISIS - Silva, Joannes Moura da (2021)
The complexity of the current technical period manifests itself in different ways and can also be seen in the production of products that crosses all existing territorial borders, while also (re)building relationships between the poles of production, distribution and consumption, in addition to reconfigure the relations between the countryside and the city. Therefore, we aim to analyze the use of the territory through the productive spatial circuit of dairy products and its circle of cooperation considering the performance of Laticínio Belo Vale - Isis. While the spatial circuit of dairy production is common, we can infer that an Isis company uses the territory due to its expansion and articulations, whether on a state or regional scale. Thus, the territory becomes regulated through its interests, such as, for example, logistics systems, such as infrastructures that make transport systems viable by interconnecting distribution centers to industrial units, milk producers, etc. as well as the agents that make up the circuit's cooperation circle, such as banks, research institutions, technical assistance, etc. Furthermore, understanding the spatial circuit of production and its respective circles of cooperation in space allows for a better analysis of how films are productive of dairy production and how the use of territory takes place. Thus, we also reflect on the changes that have taken place in the dairy sector and how they behave within the Circuit analyzed here, considering that the central productive activity is coordinated by material and immaterial flows, as well as by rejecting between geographically dispersed stages , materializing its actions in the territory.